Lymphadenitis caused by Legionella sainthelensi infection: a case report and literature review - Cangjian Zhang; Minlei Zhao (Frontiers in Medicine)
BackgroundLegionella infection is a group of bacterial diseases caused by species of the Legionella genus, the most notable of them being Legionnaires’ disease and Pontiac fever. Legionnaires’ disease primarily affects the lungs, with the respiratory and gastrointestinal systems being the most commonly affected. Legionella may cause multisystem involvement, according to this study. In this report, we present a rare case of lymphadenitis caused by Legionella sainthelensi, aiming to raise awareness of atypical manifestations and uncommon sites of Legionella infection.Case presentationWe present the case of a 43-year-old man who was admitted to the hospital for a week due to fever and enlargement of the cervical lymph nodes. He was diagnosed with L. sainthelensi lymphadenitis, which was treated with azithromycin and lymph node puncture and drainage.ConclusionFor patients with Legionella lymphadenitis, multiple etiological tests should be performed as early as possible to confirm the infectious pathogen. Early intervention with appropriate intravenous antibiotics and lymph node drainage is critical to improve the cure rate.